2020
DOI: 10.4240/wjgs.v12.i6.269
|View full text |Cite
|
Sign up to set email alerts
|

Role of micronutrients in staging of nonalcoholic fatty liver disease: A retrospective cross-sectional study

Abstract: BACKGROUND Nonalcoholic fatty liver disease (NAFLD) presents high incidence throughout the world and has been progressively increasing in prevalence. This disease has a heterogeneous natural history, including simple steatosis, nonalcoholic steatohepatitis (NASH), and cirrhosis. The factors that determine its evolution to more severe forms of the disease are still poorly understood, and micronutrients with antioxidant potential may be involved in the pathophysiology of the disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The potential mechanisms of vitamin B1 and vitamin B12 in NAFLD remains unclear, and findings from clinical studies are scarce ( 8 ). Higher serum levels of vitamin B12 were positively correlated with the severity of steatosis and fibrosis in 614 Brazilian patients ( 34 ). Dietary intakes of vitamin B1 and vitamin B12 were also found higher in patients with NAFLD patients than controls in 120 adult Jordanians ( 25 ) and 101 Canadians ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms of vitamin B1 and vitamin B12 in NAFLD remains unclear, and findings from clinical studies are scarce ( 8 ). Higher serum levels of vitamin B12 were positively correlated with the severity of steatosis and fibrosis in 614 Brazilian patients ( 34 ). Dietary intakes of vitamin B1 and vitamin B12 were also found higher in patients with NAFLD patients than controls in 120 adult Jordanians ( 25 ) and 101 Canadians ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study declared remarkable vacuolation of hepatocytes at both light and electron microscopic levels; this was explained by Barabara and Mindigulo [45] , who reported that zinc deficiency results in lipid deposition in hepatocytes; a clinical condition known as nonalcoholic fatty liver diseases. They also added that dietary zinc deficiency results in endoplasmic reticulum stress with dysfunction of enzymes needed for hepatic lipid metabolism with subsequent fatty liver development, which may end to liver fibrosis [46] . In view of such findings, most light microscopic observations, including vacuolation and ultrastructural demonstration of lipid deposition within hepatocytes in all age groups suffering from zinc deficiency, could be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the intake of vitamin B12 should be given great attention, especially its impact on NAFLD. Moreover, some study designs, including cross-sectional and case-control studies, have evaluated the association between vitamin B12 and NAFLD (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Several studies implicated positive association between vitamin B12 and NAFLD (12,16,20,21), whereas others indicated inverse association (10,13,19) or no association (11,14,15,17,18,22).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some study designs, including cross-sectional and case-control studies, have evaluated the association between vitamin B12 and NAFLD (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Several studies implicated positive association between vitamin B12 and NAFLD (12,16,20,21), whereas others indicated inverse association (10,13,19) or no association (11,14,15,17,18,22). Notably, a latest systematic review and meta-analysis comprising 361 NAFLD subjects and 510 controls demonstrated no association of vitamin B12 concentrations with risk of NAFLD (23).…”
Section: Introductionmentioning
confidence: 99%